Influence of intrinsic and extrinsic motivation on higher education performance: mediating effect of quality culture - Iqbal, Shahzaf; Razalli, Mohd Rizal; Taib, Che Azlan Bin (Frontiers in Education, 2023)
This study intends to investigate the effects of intrinsic and extrinsic motivation of faculty on higher education performance through quality culture in public and private universities of Pakistan. The study uses a nationwide survey approach, while data is collected from administrative managers through online and in-person questionnaires using stratified random sampling techniques. Of the 150 distributed questionnaires, 105 are considered valid, while the data is analyzed through the PLS-SEM. The results revealed the significant effect of intrinsic motivation and quality culture on higher education performance, and of intrinsic and extrinsic motivation on quality culture; however, the effect of extrinsic motivation on higher education performance is not empirically supported. Besides, quality culture is found to be a statistically significant mediator in the relationship between intrinsic motivation and higher education performance, and extrinsic motivation and higher education performance. The relatively smaller sample size and reliance on administrative managers as the sole respondents are the possible weaknesses of this study. This study has expanded the theoretical and empirical understanding by introducing intrinsic motivation and extrinsic motivation as predictor variables in relation to higher education performance and implicating quality culture as a mediator. This study has important implications for policymakers, administrators, and quality managers to focus on employees' motivation to create a quality culture, which in turn will improve the performance of their respective organizations.